M.Si Transformasi Kolam Terbengkalai menjadi Budidaya Aquaponik - Nurmawati, Nurmawati; Saputra, Dival Arya; Wardani, Petty Wahyu; Pramana, Muhammad Ardi Dwi; Hidayah, Vicky; Ramadhan, M. Rizky; Makarim, Hidayat; Amalia, Hanna (Jurnal Pepadu, 2025)
The agriculture and fisheries sectors are the 2 main sectors that support increasing food security in Indonesia. A new breakthrough that combines both sectors is the aquaponic cultivation system. This community service activity aims to utilize abandoned pools in the RT. 13, Damai Baru Village, Balikpapan, has become aquaponic cultivation to help the local community meet household food needs. The methods used are location surveys, problem identification, partner coordination, program outreach, creation of aquaponic cultivation ponds, and evaluation. The series of transformations carried out include designing, cleaning and increasing the size of the pool (length, width, and depth), adding a protective roof and hydroponic pipes, spreading fish seeds and water spinach, and educating on aquaponic maintenance. The resulting pond transformation has a size of 3.2 x 1.8 x 1.5 meters and 48 hydroponic planting holes. The aquaponic cultivation used is a combination of catfish and water spinach. Keywords: Aquaponics, Cultivation, Hydroponics, Catfish, Water Spinach